First record of hawker dragonflies from Eocene Baltic amber (Odonata: Anisoptera: Gomphaeschnidae) - Pinkert, Stefan; Bechly, Günter; Nel, André (Zootaxa, 2017)
Based on three specimens, the first record of hawker dragonflies from Baltic amber is described in a new genus with two new species: Elektrogomphaeschna peterthieli gen. et sp. nov. and E. annekeae sp. nov.. They belong to the family Gomphaeschnidae and are tentatively attributed to the extinct subfamily Gomphaeschnaoidinae. The latter was previously only known from Cretaceous fossils and is here shown to have survived the K-Pg mass extinction event. This discovery also confirms the still higher diversity of Gomphaeschnidae during the Paleogene compared to the Neogene that was dominated by the more derived Aeshnidae sensu stricto.